Just managing? what it means for the families of austerity Britain - O'Brien, Mark; Kyprianou, Paul; Open Book Publishers (Open Book Publishers, 2017)
"The 'just about managing'. 'Hardworking families'. 'Alarm-clock Britain'. In recent years British political discourse has been filled with these slogans, as politicians claim to speak on behalf of families who are in work, but struggling to get by. This book allows us to hear from some of these families directly. At a time when the impact of austerity is more relevant than ever, Just Managing? cuts through the debates and sloganeering to give some of the real people behind the headlines and statistics a chance to tell their stories. It tracks the lives of thirty working families in Liverpool over one year, as they struggle to manage on incomes at or around the National Minimum Wage. Their accounts are placed within the economic and political context that has shaped their experiences and that of millions of other working families across the country. This book is required reading for anyone seeking to understand what life is like at the sharp end of 'austerity Britain'."--Publisher's website.
Preface -- PART I: BACK TO THE FUTURE? 1. Understanding Poverty: Then and Now 2. The Getting By? Study -- PART II: THE BIG ISSUES 3. Money Matters 4. Working Life 5. Meeting Basic Needs 6. Home and Family Life -- PART III: JUST MANAGING? PERSPECTIVES ON POVERTY 7. Family Views: 'Who's to Blame?' 8. Liars, Thieves and Honest Scousers -- Appendix I: How the Research Was Conducted -- Appendix II: Family Circumstances and Spending -- References -- Index.
Available through Open Book Publishers.
Includes bibliographical references (pages 225-230) and index.
Mode of access: World Wide Web.
Keywords: Income distribution -- Great Britain; Poverty -- England -- Liverpool -- Case studies; Great Britain -- Economic conditions -- 21st century; Great Britain -- Social conditions -- 21st century; Liverpool (England) -- Economic conditions -- Case studies; Liverpool (England) -- Economic conditions -- 21st century